Pengaruh Latihan Pernapasan terhadap Pemulihan Pasien Covid-19 - Ariana Widyastuti; Meynur Rohmah; Zahrah Maulidia Septimar (Syntax Corporation Indonesia, 2021)
Corona virus disease 2019 (Covid-19) is a new disease has never been previously identified in humans. Covid-19 can be transmitted from human to human, including through coughing/sneezing (droplets). The purpose of this study was to determine the effect ofbreathing exercises for the recovery of covid-19 patients. Research method is quantitative with pre-test and post-test experimental. The sampling technique probability sampling using random sampling. Data analysis uses the SPSS with t-test statistics, kai squared with the limit of significance () used in this study is 0.1. The results of the characteristics control group as 40 respondents with a pre-test of 2.25 (SD = 0.809) and a post-test of 2.00 (SD=,816). while the characteristics control group of 40 respondents with a pre-test were 2.12 (SD = .686), after breathing exercises were 1.05 (SD = .221). The Paired Samples Test results is that mean value is different between the average before and after being given early mobilization, the statistical value is p = 0.000 (p <0.1), there is an effect of breathing exercises for the recovery of covid-19 patients